(untitled) (Research, Society and Development, 2020)
In natura sugarcane juice or garapa is one of the derivatives of sugarcane and is a tasty and energetic drink. The addition of acid fruits to the sugarcane juice is quite common, giving the product a refreshing flavor and softening its sweetness. The present study aimed to evaluate the sensorial quality of beverages elaborated by mixing sugarcane juice and fruits pulp, among high school students at IFNMG – campus Salinas. The samples were prepared for the flavors of passion fruit, tamarind, and caja, adding pulp in the proportions of 5, 7.5 and 10 mL per 100 mL of sugarcane juice, and a preference-ranking test was applied to 30 untrained panelists. Based on the result of this test, samples of the beverage with the preferred pulp concentration for each flavor were prepared. The acceptance test was applied to 88 panelists in the same study group. For the preference-ranking test, this analysis showed that there was no significant difference (p ≥ 0.05) between the samples in any of the three flavors and concentrations evaluated. However, the highest absolute values were obtained by the samples of passion fruit and tamarind at 5% of pulp and caja at 7.5% of pulp. Regarding the acceptance test, there was no significant difference (p ≥ 0.05) between samples. In the evaluation of the overall impression, the scores were between “like moderately” and “like extremely”, which shows a great acceptance for these products. Also, the most accepted flavor was caja at 7.5%. The purchase intention was evaluated as “probably buy” and “certainly buy” and the highest purchase intention was also for the sample of caja at 7.5%. Therefore, this study contributes to a greater appreciation of the fruits from the semi-arid and to adding value to the sugarcane juice.